2008
DOI: 10.4103/0019-5359.44020
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sex hormone binding globulin and metabolic syndrome parameters in premenopausal obese women

Abstract: BACKGROUND AND AIMS:The aim of this study was to determine sex hormone binding globulin (SHBG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…This phenomenon suggested that disorder of internal sex hormones might be responsible for the formation of TN. The wave of sex hormone binding globulin (SHBG) might play an important role in this process [29, 30]. Our data indicates that the prevalence of TN in both men and women increases gradually with age, which is consistent with previous studies [31, 32].…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon suggested that disorder of internal sex hormones might be responsible for the formation of TN. The wave of sex hormone binding globulin (SHBG) might play an important role in this process [29, 30]. Our data indicates that the prevalence of TN in both men and women increases gradually with age, which is consistent with previous studies [31, 32].…”
Section: Discussionsupporting
confidence: 91%
“…This study also found that the results show strong relationships between SHBG and BFI in obese postmenopausal women with exercise (results not shown). Similar findings were reported by Akin et al, 33 who aimed to determine SHBG concentrations in premenopausal obese women and features of the metabolic syndrome. Their low SHBG group was significantly heavier and had higher BMI values with higher WC than the high SHBG group.…”
Section: Discussionsupporting
confidence: 78%
“…While this study was limited to male participants, a low SHBG has also been shown to be associated with obesity [77], [78], insulin resistance [78], [79], and the metabolic syndrome in women [80]. SHBG is a marker of de novo hepatic lipogenesis in both men and women [81], [82].…”
Section: Discussionmentioning
confidence: 98%